New Echocardiographic Findings Correlate with Intramyocardial Inflammation in Endomyocardial Biopsies of Patients with Acute Myocarditis and Inflammatory Cardiomyopathy. (20th March 2013) - Escher, Felicitas; Kasner, Mario; Kühl, Uwe; Heymer, Johannes; Wilkenshoff, Ursula; Tschöpe, Carsten; Schultheiss, Heinz-Peter
Abstract : Background . The diagnosis of acute myocarditis (AMC) and inflammatory cardiomyopathy (DCMi) can be difficult. Speckle tracking echocardiography with accurate assessments of regional contractility could have an outstanding importance for the diagnosis. Methods and Results . N = 25 patients with clinically diagnosed AMC who underwent endomyocardial biopsies (EMBs) were studied prospectively. Speckle tracking imaging was examined at the beginning and during a mean follow-up period of 6.2 months. In the acute phase patients had markedly decreased left ventricular (LV) systolic function (mean LV ejection fraction (LVEF) 40.4 ± 10.3 %). At follow-up in n = 8 patients, inflammation persists, correlating with a significantly reduced fractional shortening (FS, 21.5 ± 6.0 %) in contrast to those without inflammation in EMB (FS 32.1 ± 7.1 %, P < 0.05 ). All AMC patients showed a reduction in global systolic longitudinal strain (LS, − 8.36 ± − 3.47 %) and strain rate (LSR, 0.53 ± 0.29 1/s). At follow-up, LS and LRS were significantly lower in patients with inflammation, in contrast to patients without inflammation (− 9.4 ± 1.4 versus − 16.8 ± 2.0 %, P < 0.0001 ; 0.78 ± 0.4 versus 1.3 ± 0.3 1/s). LSR and LS correlate significantly with lymphocytic infiltrates (for CD3 r = 0.7, P < 0.0001, and LFA-1 r = 0.8, P < 0.0001 ). Conclusion . Speckle tracking echocardiography is a useful adjunctive assisting tool for evaluation over the course of intramyocardial inflammation in patients with AMC and DCMi.